أثر القيادة الرشيقة على الاداء الوظيفي دراسة ميدانية على جهاز استثمار النهر الصناعي سهل بنغازي (Sirte University Journal of Humanities, 2024)
This study aims to identify the level of agile leadership practice among employees of the Great Man-Made River Investment Authority, Benghazi Plain, and to know their level of job performance and to determine the impact of agile leadership on job performance. The study community was limited to employees of the Great Man-Made River Investment Authority, Benghazi Plain, and a simple random sample was taken according to Morgan's table. In this study, the descriptive analytical approach was relied upon, and the basic data for this study were collected through a questionnaire and the use of the statistical packages program (SPSS) by computer in analyzing the study data, represented in frequency tables, arithmetic means, standard deviations, and regression coefficient to determine the effect between the study variables. The study concluded that there is a positive correlation between the agile leadership variable and job performance, as well as a statistically significant effect on job performance.
Keywords: agile leadership; job performance; Benghazi plain; Sulug, GMMR.